(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article discusses terminology, in particular, economic terms, problems and recommendations for their formation in the Uzbek language, as well as problems with the translation of terms into Uzbek. In general, in the Uzbek terminological system, a lot of researches have been done, and it is important to improve the terminology of each field, to interpret their meaning at the level of modern requirements.